The protective effect of ettlingera coccinea (TUHAU) against autoxidation-induced ox brain homogenate - Nur Najmi Mohamad Anuar; Jamaludin Mohamed; Erni Norfardila Abu Hanipah; Nor Janna Yahya; Esther Mathias Ajik; Izatus Shima Taib (Penerbit Universiti Kebangsaan Malaysia, 2018)
Oxidative stress involved in various pathological conditions. Plants have been proven to act as a natural exogenous antioxidant. The aim of this research is to investigate the protective effects of Etlingera coccinea leaves aqueous extract on autoxidation-induced ox brain homogenate. The brain homogenate was divided into 7 groups: control group with PBS solution, positive control group with 100 μg/ml ascorbic acid, test group with 25, 50, 100, 200 and 400 μg/ml of E. coccinea. The antioxidant potential of E. coccinea aqueous extract has been evaluated by antioxidant capacity assay such as Total phenolic content (TPC), radical scavenging assay (DPPH) and ferric reducing antioxidant power (FRAP). Malondialdehyde (MDA), superoxide dismutase (SOD) and glutathione (GSH) were also measured at 0 hr and 1 hr after 37°C water bath incubation to determine the antioxidant status and oxidative damage. TPC assay showed (4.85 ± 0.28) mg GAE/g of dry weight of E. coccinea leaves. Based on DPPH and FRAP assay, E. coccinea aqueous extract showed a dose-dependent antioxidant activity. MDA level in the 50 μg/ml E. coccinea was significantly lower compared to the other groups (p < 0.05). The SOD activity was significantly increase in 400 μg/ml E. coccinea (p < 0.05) compared to other groups. E. coccinea at the dose of 25 μg/ml and 50 μg/ml showed significant increase in GSH level compared to other groups (p < 0.05). In conclusion, 25 μg/ml and 50 μg/ml of E. coccinea leave aqueous extracts exhibited a potential protective effect on autoxidation-induced ox brain homogenate.